Cascade Synthesis from Cyclohexane to ϵ‐Caprolactone by Visible‐Light‐Driven Photocatalysis Combined with Whole‐Cell Biological Oxidation. (5th March 2020) - Li, Peilin; Ma, Yunjian; Li, Yongru; Zhang, Xizhen; Wang, Yonghua
Abstract: Cyclohexane was directly oxy‐functionalised to ϵ‐caprolactone through a cascade reaction sequence combining visible‐light‐driven photocatalysis with cyclohexanone monooxygenase (CHMO) whole‐cell biocatalysis. Two available photocatalysts, Au‐doped TiO2 (Au‐TiO2 ) and graphitic carbonitride (g‐C3 N4 ), were evaluated in the experiment and some optimisations to the cascade reaction were applied. In stepwise mode, the highest degree of conversion from cyclohexanol to ϵ‐caprolactone can be up to 41 %, with use of g‐C3 N4 . The cascade reaction from cyclohexane to ϵ‐caprolactone is achievable under a light intensity of 149 μW cm −2 . Abstract : Photoenzymatic combinations : Cyclohexane was oxy‐functionalised to ϵ ‐caprolactone directly through a cascade reaction sequence combining visible‐light‐driven photocatalysis with whole‐cell biocatalysis. Two photocatalysts, Au‐doped TiO2 and graphitic carbonitride, were used in the reaction. After expression of cyclohexanone monooxygenase (CHMO) in E. coli, the whole cells were used as biocatalyst.